Determinação de Cd, Co, Cr, Cu, Ni e Pb em cosméticos infantis empregando técnicas espectroanalíticas - Augusto, Amanda dos Santos (2014)
In this study were developed two methods for sample preparation: one for children s eye shadow and another for chidren s lipstick. In the optimizing process, variables such as nitric acid concentration (2 or 7 mol L-1), sample mass (100 or 250 mg), heating time (1 or 3 hours) and concentration of Triton X-100 (5 or 25%) were investigated. The instrumental parameters of ICP OES were optimized in order to find a good working condition for the analytes determination. In the beginning it was performed a fractional factorial design 29- 5 (nine variables) and, after variables selection, a fine adjustment using Central Composite and Doehlert designs was made to study the most important variables (radio frequency power and nebulizer gas flow rate). In order to evaluate the regression models proposed, responses like LOQ and recovery for each analyte and in each view mode (radial and axial) were taken into consideration using desirability function. From the generated models it was possible to find the compromise condition with radio frequency power of 1200 W and a nebulizer gas flow rate of 0.825 L min-1. The methods developed for the preparation of the samples were applied to 22 samples of children cosmetics (14 eye shadows and 8 lipsticks). The analytes were determined using ICP OES (Cd, Co, Cr, Cu and Ni) and GF AAS (Pb). The majority of the concentrations obtained were lower than the international normatives, but the Pb values ranged from <LOQ to 44 mg kg-1 in some samples. Exploratory analysis using the emission spectra from LIBS was performed and similarity among the samples was observed.